The ’political’ brain. Marxian presuppositions in Vygotsky’s psychology - Garofalo, Pietro (Rivista Italiana di Filosofia del Linguaggio, 2012)
Many psychological theories have analyzed cognitive processes such as perception and reasoning, based on the methodological individualism. However those theories have not provided an explanation of the complex social behaviors characterizing the Homo sapiens specie‘s life. Vygotsky, differently to other contemporary psychologists, recognized the role of the social relations on explaining the human cognition. My aim is to investigate why Vygotsky was able to provide a psychological theory strongly linked to the social context. The main hypothesis is that Vygotsky founded his theory on the Marxian anthropology, which primarily focused on the economical and political forms of life. This linkage enabled Vygotsky to develop a psychological theory that can explain the complexity of social and political life by theorizing the concept of “political” brain, which is open to incorporate the “political” dimension